2003
DOI: 10.1021/jf030181z
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Tea (Camellia senensis) Catechins Is Required for Optimal Inhibition of Induced CYP1A Expression by Green Tea Extract

Abstract: It was previously demonstrated that the commercial green tea extract Polyphenon 100 (P100), and to a lesser extent (-)-epigallocatechin-3-gallate (EGCG), partially antagonizes 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)-induced transcription of human CYP1A1 (Williams, S. N.; Shih, H.; Guenette, D. K.; Brackney, W.; Denison, M. S.; Pickwell, G. V.; Quattrochi, L. C. Chem.-Biol. Interact. 2000, 128, 211-229). Here, P100 is compared to a reconstituted mixture of the four major tea catechins (referred to as P100R) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…H. Wu et al 2003). In our study, male rats were more severely affected, which is consistent with previous studies (Raederstorff et al 2003; Takami et al 2008;S. N. Williams, Pickwell, and Quattrochi 2003; Yoshino et al 1994).…”
Section: Discussionsupporting
confidence: 93%
“…H. Wu et al 2003). In our study, male rats were more severely affected, which is consistent with previous studies (Raederstorff et al 2003; Takami et al 2008;S. N. Williams, Pickwell, and Quattrochi 2003; Yoshino et al 1994).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, a mixture of the four tea catechins (Polyphenon 100) and individual tea catechins differently modulated human cytochrome P450 1A expression. The underlying mechanisms of increased effectiveness of green tea and a catechin mixture compared to single catechins were not elucidated in this study [242]. …”
Section: Reviewmentioning
confidence: 99%
“…For instance, Horie et al reported that the EGCG worked synergistically with EC to inhibit the gastric carcinoma cells growth and induce apoptosis [35]. Besides, it was also found that the efficacy of the mixture of EGCG, EGC, ECG and EC was higher than EGCG alone in inhibiting HepG2 cell growth [36].…”
Section: Discussionmentioning
confidence: 99%